REDUCED FLUID AS A FACTOR IN METAL MIGRATION - Gottikh R.P.; Pisotskiy B.I.; Burmistenko Y.N.; Spiridonov A.I. (My University, 1988)
Judging by petrographic and f-radiographic data, a feature specific to such fluid is the presence in it of uranium. That explains why different categories of carbon compounds, generated as a result of its breakdown, also contain uranium. The aim of this work was to further study the trace-element composition of the fluid, the forms of their transport in it and their distribution patterns in the products of its breakdown. For this purpose, instrumental neutron-activation analysis was used. To determine the trace-element composition of the fluid, two quartz specimens were analyzed simultaneously. To study the aqueous phase, material from decrepitated vacuoles was first washed in doubly distilled water under nitrogen; then it was evaporated and analyzed. Study results ore discussed.